The negative pressure wound therapy may salvage the infected mesh following open incisional hernia repair. (January 2021) - Boettge, K.; Azarhoush, S.; Fiebelkorn, J.; De Santo, G.; Aljedani, N.; Ortiz, P.; Anders, S.; Hünerbein, M.; Paasch, C.
Abstract: Background: s: Incisional hernias may occur in 10–25% of patients undergoing laparotomy. In cases of a surgical site infection (SSI) after incisional hernia repair (IHR) secondary operative intervention with mesh removal are often needed. There is only minimal data available in the literature regarding the treatment of a wound infection with negative pressure wound therapy (NPWT). Conducting the study at hand, we aimed to provide more evidence on this topic. Methods: From April to June 2020 a monocentric retrospective study has been performed. Patients who underwent NPWT due to a SSI with mesh involvement following open IHR from 2007 to 2020 were included. The primary endpoint was the mesh removal rate in the end of NPWT. Main secondary endpoints were the duration of NPWT and the amount of NPWT procedures. Results: The data of 30 patients were extracted. The average age was 65.9 years (9.9). A total of 13 individuals were male and 17 females. The BMI was on average 31.1 kg/m 2 (4.9). All patients received a polypropylene mesh. The average duration of NPWT was 31.3 days (22.1). The first wound revision with initiation of a NPWT was conducted on average 31.1 days (34.0) after IHR. The average amount of NPWT procedures was 8.3 (7.2). In 5 of 30 patients (16.6%) the mesh was removed (Open sublay group n = 4 (36.34%) vs. open onlay group n = 1 (5.26%), p = 0.047). Conclusion: In cases of SSI following IHR the NPWT may facilitate mesh selvage. Further trials with a larger sample size are mandatory to confirm our hypothesis. Highlights: As one of a main complication SSI may occur in up to 30% of cases following incisional hernia repair. The mesh is often removed in cases of a SSI. NPWT may salvage mesh removal in cases of mesh infection.